Anticoagulant therapy and altered tissue factor expression protect against experimental placental and cerebral malaria. - Alicer K Andrew; Tara C Bracken; Nicole Nazario-Maldonado; Brittany N Russ; Kathyrn T Gonzalvo; Benjamin M Brainard; Nigel Mackman; Julie M Moore (PLoS Pathogens, 2025)
Severe malaria remains a major public health concern in regions of moderate to high Plasmodium falciparum transmission. Women and young children are especially vulnerable to two clinical manifestations of severe P. falciparum malaria, known as placental malaria (PM) and cerebral malaria (CM). Both PM and CM have been characterized as procoagulant states; however, the role of coagulation in galvanizing poor health outcomes is incompletely understood. Moreover, the contribution of tissue factor (TF), the primary driver of the extrinsic pathway of coagulation, to the pathogenesis of PM and CM has not been fully explored. This work utilizes experimental murine models of PM (EPM) and CM (ECM) to explore the impact of anticoagulant treatment and tissue-specific or global reduction in TF expression on disease outcomes. In EPM, we show that treatment of wild-type mice with dalteparin, an anticoagulant class that is safe to use in humans during pregnancy, prevented malaria-induced pregnancy loss, significantly improved embryo viability, and decreased placental fibrin deposition at midgestation. Similarly, mice deficient for endothelial/hematopoietic TF, TFTie2Δ, exhibited a superior ability to maintain their pregnancies at midgestation compared to TF-intact littermate controls, who unequivocally lost their pregnancies. Uterus weight and embryo viability were significantly improved in TFTie2Δ dams despite experiencing similar parasite burdens as controls. In ECM, dalteparin treatment promoted preservation of the blood-brain barrier (BBB) and protected against the development of neurological signs. Likewise, mice genetically modified to have low TF expression (LTF) exhibited less perivascular leakage in the brain and significantly increased survival probability compared to their littermate controls (TFhet). Together, these data show that anticoagulant treatment can successfully protect against poor health outcomes in two murine models of severe malaria and identify a potentially universal role of TF in driving severe malaria pathogenesis.